Determining Key Factors Influencing Purchase Intentions in Halal-Certified Stores in Non-Muslim Country - Wicaksono, Tutur (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2024)
This study aims to identify and analyze the key factors influencing purchase intentions among consumers in halal-certified stores located in a non-Muslim country. A quantitative research design was employed, utilizing a structured closed-ended questionnaire distributed to a sample of 384 consumers who had previously shopped into halal-certified stores. The data were analyzed using an analytical hierarchy process (AHP) framework and statistical methods, including descriptive statistics, to identify the key factors of halal-certified store purchase intentions. The results reveal that the finding reveal that product quality (score = 4.41), halal awareness (score = 4.31), and halal certification (score = 4.27) are the top three factors influencing customer purchase intention for halal-certified stores in non-Muslim countries. This study provides valuable insights for retailers and marketers in non-Muslim countries seeking to enhance the appeal of halal-certified stores. Focusing on improving product quality, halal awareness, and halal certification. businesses can better cater to consumers’ needs and preferences. This study contributes to the existing literature by exploring the dynamics of halal consumption in non-Muslim contexts, highlighting the importance of understanding consumer behavior in multicultural environments.